Lone eagle - Steel, Danielle (London : Corgi Books, 2002)
The phone call came on a snowy December afternoon. Kate was certain it was Joe, the brilliant, visionary man who had been her soulmate, her driving force since the night they met, almost thirty-four years before. What she got was the one call she had never wanted, and didn't expect.
Keywords: Air pilots -- Fiction; Love stories